The utility of monitoring end-tidal carbon dioxide in emergency department to predict inhospital mortality of patients presenting with nontraumatic shock: A prospective observational study - R Abhiraj; Meera Ekka; Aravind Sreekumar; Praveen Aggarwal; Nayer Jamshed; Sanjeev Kumar Bhoi; Maroof Ahmed Khan (Turkish Journal of Emergency Medicine)
OBJECTIVES: We aimed to identify the ability of end-tidal carbon dioxide (EtCO2) to predict inhospital mortality of patients presenting to the emergency department (ED) with nontraumatic circulatory shock. We also attempted to assess the correlation between EtCO2 and other traditional vital signs and laboratory parameters in this patient population at different time points during their resuscitation. METHODS: This was a single-center prospective observational study conducted among patients with nontraumatic circulatory shock who presented to the ED of a tertiary care teaching institute in India. EtCO2 measurement was done using mainstream capnography in both intubated and nonintubated patients at presentation and at 120 min of resuscitation. Heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure (MAP), respiratory rate, oxygen saturation, and laboratory parameters (lactate, base deficit [BD], and partial pressure of carbon dioxide) were measured at the same time points. All patients were followed up till hospital discharge. RESULTS: One hundred and ten patients were recruited to the study. An EtCO2 of ≤ 23 mm Hg at presentation was 87% sensitive (95% CI: 73-95 %) and 43% specific (95% CI: 31-56 %) in predicting in-hospital mortality of patients presenting with no-traumatic circulatory shock in emergency department [area under curve (AUC): 0.735 (95% CI: 0.638-0.832, p<0.001)]. EtCO2 ≥23 mmHg at presentation had a significant predictive value on the risk of in-hospital mortality with an adjusted odd’s ratio of 0.08 (95% CI: 0.02–0.3, P < 0.001). EtCO2 values at presentation and 120 min as well as the change between the time points showed statistically significant weak-to-moderate positive correlations with corresponding values of MAP and BD. Similarly, a significant negative correlation was demonstrated with lactate levels at the same time points. CONCLUSION: EtCO2 values at presentation are an independent predictor of inhospital mortality of patients with circulatory shock of nontraumatic etiology presenting to the ED.